University journalism study programme in the context of higher education and science reform - Vaišnys, Andrius (Žurnalistikos tyrimai, 2009)
The reform of higher education and science in Lithuania has brought new challenges: study programmes will have to be restructured according to new laws and it will be necessary to improve what has already been created. Therefore, the prospects for the discipline of journalism studies should be explored in the context of higher education and science reforms in Lithuania, with the main focus on the following aspects: 1) How to understand the aims and tasks of university schools of journalism in our modern networking society (original participation in the network of schools); 2) How to achieve quality in university schools and their studies (how and what research programmes should be supported and implemented); 3) What is the future of university studies, considering university or universities traditions, resources, and the needs of both graduates and the market. Keywords: history and changes in journalism studies, higher education and science reform, media research, university studies, creative communication, political communication, and freedom of the press.